New species, new combinations and synonymies of Neotropical Galerucini (Coleoptera, Chrysomelidae, Galerucinae) - Moura, Luciano De A. (Zootaxa, 2016)
New species of Neotropical Galerucini are described and illustrated: Caraguata onca sp. nov., from southern Brazil (Rio Grande do Sul) and northern Argentina (Chaco); and Yingaresca cabrerae sp. nov., from Argentina (Misiones). Galerucella transversicollis Jacoby, 1886 is integrated to Yingaresca Bechyné. Two species originally described in Ophraella Wilcox are also transferred to Yingaresca: Yingaresca limonensis (Bechyné, 1997) comb. nov. and Yingaresca magdalia (Bechyné, 1997) comb. nov. Metrogaleruca obscura paraensis (Bechyné & Bechyné, 1961) is considered a synonym of Metrogaleruca obscura (Degeer, 1775).